Strategi Harga Penawaran Tender pada Proyek Konstruksi Dengan Memperhitungkan Faktor Resiko - Wulandari, Annisa; Handayani, Elvira; Dony, Wari (Universitas Batanghari Jambi, 2024)
To get a construction project through a process called a tender (auction). This process is very crucial in determining the party who will carry out the construction project. For this reason, a strategy is needed, one of which is determining the offering price. The bid price really determines the possibility of winning a construction project as well as the size of the profit or profit on the construction project. One of the problems that is often encountered is determining the offering price which should not be too high or too low. The aim of this research is to analyze the mark up value in construction project tenders at the Jambi City Electronic Procurement Institute (LPSE) using the Friedman Method, Gates Method, and Ackoff & Sasieni Method bidding strategy approaches and compare the strategic approaches that produce optimum mark up values so that can be used as an alternative in determining the offering price. The data used in this research is auction data for construction work that has been completed at Electronic Procurement Institute (LPSE) Jambi in 2022 using three statistical approaches, namely multi discrete distribution, multi normal distribution and single normal distribution. In this research it can be concluded that the Friedman Method and Ackoff & Sasieni Method produce the lowest optimum mark up value, while the Gates Method produces the highest optimum mark up value.